2017
DOI: 10.1111/jav.01295
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relatedness of co‐occurring waterbird communities: a test of Darwin's competition‐relatedness hypothesis

Abstract: The competition–relatedness hypothesis of Darwin states that competition is greater among species that are phylogenetically closely‐related, and such species will tend to appear in separate communities (i.e. the species within communities will be phylogenetically overdispersed). Many studies have tested (and mainly refuted) this hypothesis for plant and bacterial communities. Results for the few studies with avian species are not conclusive. We tested Darwin's hypothesis for waterbirds using a set of open, art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This suggests that in all wetland types (except for Art) the most abundant breeding species tend to be more functionally different from one another than the most abundant wintering species. This may indicate lower inter‐specific competition during winter, although Sebastián‐González and Green (2017) found no evidence in Afp for a seasonal change in interspecific competition based on co‐occurrence of closely related species. Similarly, Bidwell, Green, and Clark (2014) found no evidence that interspecific competition influences spatial distribution of breeding ducks in a prairie wetland complex.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This suggests that in all wetland types (except for Art) the most abundant breeding species tend to be more functionally different from one another than the most abundant wintering species. This may indicate lower inter‐specific competition during winter, although Sebastián‐González and Green (2017) found no evidence in Afp for a seasonal change in interspecific competition based on co‐occurrence of closely related species. Similarly, Bidwell, Green, and Clark (2014) found no evidence that interspecific competition influences spatial distribution of breeding ducks in a prairie wetland complex.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, although located in former temporary marsh areas, they had an artificial hydrology and relatively stable water levels. Five of them were extensive fish ponds used to raise estuarine fish of commercial value, in which the food supply available to waterbirds has been relatively well studied (Rodríguez‐Perez & Green, 2012; Sebastián‐González & Green, 2017; Walton, Vilas, Cañavate, et al., 2015; Walton, Vilas, Coccia, et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 300 adults of T. v. verticalis were collected during each of six visits to Veta la Palma fish ponds (VLP) in Doñana Natural Park (see Céspedes, et al., 2019; Sebastián‐González & Green, 2017; Walton et al., 2015 for further information concerning this area, and its flora and fauna; Table 1). We measured temperature, conductivity, and salinity by spot sampling in situ using a conductivity meter (WTW® ProfiLine Cond 3,110).…”
Section: Methodsmentioning
confidence: 99%
“…We identified seasonal differences in the number of the pairs of species that exhibited non‐random co‐occurrence patterns. First, we calculated the standardized effect size of the co‐occurrence (SES.COOC):SES.COOC=false(COOCobsCOOCmeanfalse)/SDnormalcooc,where COOC obs is the observed co‐occurrence of the assemblage, COOC mean is the mean value of the co‐occurrence of all the simulated assemblages, and SD cooc is the standard deviation of the co‐occurrence values of all the simulated assemblages (Griffith, Veech & Marsh, ; Sebastián‐González & Green, ). Significance was determined at the 5% level ( p < 0.05), and we repeated the analyses using a Bonferroni correction ( p < 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the relative importance of top‐down control of basic resources has been shown to shift with climatic seasonal changes, with stronger top‐down impact during high‐diversity periods (Paszkowski & Tonn, ). Previous studies of phylogenetic assembly of wintering waterbirds have found a dominant phylogenetic clustering pattern, suggesting that waterbird assemblages are structured by similar microhabitat preferences (Sebastián‐González & Green, ). However, summer assemblages of song birds in temperate and tropical forests appear to generally be assembled by biotic interactions (Gomez, Bravo, Brumfield, Tello & Cadena, ).…”
Section: Introductionmentioning
confidence: 92%